Pemodelan status kelayakan saham di aplikasi ajaib menggunakan metode regresi logit ordinal - Nugroho, Hariawan Widi; Sediono, Sediono; Ana, Elly (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The development of the capital market cannot be separated from the contributions of investors and brokers. From 2018 until the end of September 2021, the number of investors has increased every year. PT. Ajaib Sekuritas Asia is one of the brokerage companies listed on the IDX. The purpose is for modelling, analyzing, and interpreting the stock eligibility status in the Ajaib using the ordinal logistic regression with logit function. The data used in this study is secondary data which includes: RoA (Return on Assets), GPM (Gross Profit Margin), OPM (Operating Profit Margin), NPM (Net Profit Margin), and Stock Status. All data is available in the Ajaib investment application, so Ajaib is the main data source in this research. The study result indicate that there are patterns between Return on Assets, Gross Profit Margin, Operating Profit Margin, and Net Profit Margin, to the stock eligibility status. The predictability of the model reached 49.22% and the pseudo R2is 19% with an error rate of 5%. Based on the results of the study, it can be concluded that there is a pattern of relationship between the issuer's financial indicators, which include Return on Assets (RoA), Gross Profit Margin (GPM), Operating Profit Margin (OPM), and Net Profit Margin (NPM), on the feasibility status of existing shares. In the Magic investment app. A positive relationship is shown by RoA, GPM, and NPM to the logit function of stock eligibility status, while a negative relationship is only shown by OPM to stock eligibility status.